The Influence of Multiple Store Environment Cues on Perceived Merchandise Value and Patronage Intentions - Baker, Julie; Parasuraman, A.; Grewal, Dhruv; Voss, Glenn B. (Journal of Marketing, 2002)
Research on how store environment cues influence consumers' store choice decision criteria, such as perceived merchandise value and shopping experience costs, is sparse. Especially absent is research on the simultaneous impact of multiple store environment cues. The authors propose a comprehensive store choice model that includes (1) three types of store environment cues (social, design, and ambient) as exogenous constructs, (2) various store choice criteria (including shopping experience costs that heretofore have not been included in store choice models) as mediating constructs, and (3) store patronage intentions as the endogenous construct. They then empirically examine the extent to which environmental cues influence consumers' assessments of a store on various store choice criteria and how those assessments, in turn, influence patronage intentions. The results of two different studies provide support for the model. The authors conclude by discussing the results to develop an agenda for additional research and explore managerial implications.